INTRAVITREAL BEVACIZUMAB: INDICATIONS AND COMPLICATIONS - Jan, Sanaullah; Nazim, Muhammad; Karim, Samina; Hussain, Zakir (Journal of Ayub Medical College Abbottabad, 2016)
Background: Bevacizmab is still an unlicensed drug for intraocular use in spite of the fact that it has shown comparable efficacy to other anti-vascular endothelial growth factors (anti-VEGF) medications in some large sample randomized control trails. Although repackaged bevacizumab has got safety concerns but its use is growing because of easy availability and low cost. Our study focuses on the diverse and growing indications of intravitreal bevacizumab (IVB) and its ocular complications in our geographical setting. Method: This interventional case series was carried out at my private practice in Said Anwar Medical Complex, Dabgari, Peshawar, from January 2008 to July 2015. Total of 6107 injections were given to 4352 eyes. Intravitreal bevacizumab was injected in proper operating room setting. Bevacizumab injections were prepared from same vial by multiple withdrawals taking care of aseptic precautions. Follow up was done at 1 week and 20 days and adverse effects were noted. Results: Diabetic macular oedema (36%), central retinal vein occlusion (17.6%) and branched retinal vein occlusion (11%) were the top three indications of IVB. Other common indications were proliferative diabetic retinopathy (9.6%), neo-vascular glaucoma (5.9%), proliferative diabetic retinopathy with vitreous bleed (4.4%), proliferative diabetic retinopathy with tractional retinal detachment (3.7%), neo-vascular age related macular degeneration (2.9%), central serous retinopathy (1.48%) and Eale’s disease (1.48%). Endohthalmitis occurred in 3 eyes (0.069%) while retinal detachment was found in only 2 eyes (0.046%).Conclusion: Common indications of bevacizumab are diabetic macular oedema, central retinal vein occlusion and branched retinal vein occlusion. Complications like endophthalmitis and retinal detachment are rare. Keywords: Intravitreal bevacizumab, Avastin, Endophthalmitis